2023
DOI: 10.1027/1864-1105/a000354
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Benefits of Scary Play in Three Types of Horror Fans

Abstract: Abstract. Why do people seek out frightening leisure activities such as horror films and haunted attractions, and does the experience benefit them in any way? In this article, we address these questions through two separate studies. In Study 1, we asked American horror fans ( n = 256) why they like horror and identified three overall types of horror fans, which we term “Adrenaline Junkies,” “White Knucklers,” and “Dark Copers.” In Study 2, we collected data from Danish visitors at a haunted house attraction ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…In addition to the factor knowledge, we found that the more participants anticipated that reading an article would be self-relevant (i.e., relevant to their own personal situation and helping them prepare for an emergency), the more often they chose to read the article. This finding is consistent with recent empirical findings (Abir et al, 2022; Scrivner et al, 2021, 2023) that demonstrate that personal utility may play a role in the choices that people make in their consumption of both news and entertainment. The finding that the anticipated self-relevance of information can predict decisions to engage with negative information concerning others sheds interesting light on some contrasting findings in the literature on curiosity and information seeking.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to the factor knowledge, we found that the more participants anticipated that reading an article would be self-relevant (i.e., relevant to their own personal situation and helping them prepare for an emergency), the more often they chose to read the article. This finding is consistent with recent empirical findings (Abir et al, 2022; Scrivner et al, 2021, 2023) that demonstrate that personal utility may play a role in the choices that people make in their consumption of both news and entertainment. The finding that the anticipated self-relevance of information can predict decisions to engage with negative information concerning others sheds interesting light on some contrasting findings in the literature on curiosity and information seeking.…”
Section: Discussionsupporting
confidence: 92%
“…It is possible that some horror fans have different levels of empathy or compassion on average, even if this does not show up across rated enjoyment of subgenres. Scrivner et al (2022) recently identified three types of horror fans: adrenaline junkies, white knucklers, and dark copers. These three types of horror fans appear to be attracted to horror for different reasons and experience different psychological benefits from horror engagement.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Through a process of belief updating and embodied action, the brain acts to minimize any discrepancy between its predictions and its actual sensory states-a quantity known as 'prediction error'. 1 So long as the organism keeps the error in its predictions to a minimum over time, either through updating its predictions or by acting on the world to make it better fit the prediction, the organism will typically succeed in achieving the valued outcomes it aims for in acting [2][3][4][5][6][7].…”
Section: Predictive Processing Curiosity and Playmentioning
confidence: 99%
“…This is a large part of our story, but it is not the whole story. Recent work suggests that we might enjoy horror films because they allow us to explore threatening situations, and so help us to transform our unpredictable reality into a more predictable one [32,33]. The monsters that are for us such a provocative source of fear and disgust are only the creative constructs of our imaginations, and appear only on the screens and pages of works we know to be fictional.…”
Section: Predictive Processing Curiosity and Playmentioning
confidence: 99%